289 DIAGNOSTIC PATHWAY OF PATIENTS WITH CHRONIC CORONARY SYNDROME AFTER THE ISCHEMIA TRIAL PUBLICATION. (15th December 2022) - Spagnolo, Marco; Laudani, Claudio; Occhipinti, Giovanni; Agnello, Federica; Legnazzi, Marco; Scalia, Lorenzo; Mauro, Maria Sara; Rochira, Carla; Finocchiaro, Simone; Greco, Antonio; Capodanno, Davide
Abstract: Introduction: Patients with chronic coronary syndrome (CCS) can initially undergo an invasive (i.e., early referral to invasive coronary angiography [ICA]) or a conservative (i.e., anatomical or functional testing before ICA) management. The ISCHEMIA trial showed no difference between these two strategies in CCS patients with moderate-to-severe ischemia. The aim of our study was to assess whether the results of the ISCHEMIA trial impacted on the management of CCS patients. Methods: Trends in the management of patients with CCS in our centre, according to the ISCHEMIA trial publication date, were analyzed and patients categorized into pre-ISCHEMIA (before March 2020) and post-ISCHEMIA (from July 2020 to February 2022) groups, with an in-between blanking period of three months. The primary outcome was incidence of referral to ICA by coronary computed tomography angiography (CCTA). Secondary objectives included the incidence ischemia test-referred ICA, incidence of CCTA-referred ICA and subsequent percutaneous coronary intervention (PCI), incidence of ischemia test-referred ICA and subsequent PCI and incidence of CCTA-referred ICA without subsequent PCI. Differences between the pre-specified subpopulations (age ≥75 years, diabetes, chronic kidney disease [CKD], peripheral arterial disease [PAD], gender male, unstable angina, active smoking status, body mass index [BMI] >30, hypertension, family history of coronary artery disease [CAD], atrial fibrillation [AF], prior percutaneous coronary intervention [PCI], prior coronary artery bypass grafting [CABG]) and the general population of the study were tested using a regression analysis. Results: A total of 2, 365 patients were included, 487 (20.6%) and 1, 878 (79.4%) in the pre-ISCHEMIA and post-ISCHEMIA groups, respectively. There were no notable between-group differences in baseline characteristics. The primary outcome occurred more frequently in the post-ISCHEMIA group (73.5% vs. 32.5%; p<0.01). Compared to pre-ISCHEMIA, the post-ISCHEMIA group displayed less referrals to ICA by ischemia testing (31.6% vs. 52.5%; p<0.01) and more ICA referrals by CCTA with subsequent PCI (8.3% vs. 12.0%; p<0.01). There were no within-group differences in ischemia test-referred ICA and PCI, and CCTA-referred ICA without subsequent PCI. A regression analysis between the primary endpoint incidence in the general population compared to the incidence in the pre-specified subpopulations showed no significant difference in the p values for interaction. Conclusions: In the first two years from publication, the ISCHEMIA trial significantly impacted on the decision-making algorithm for patients with CCS, increasing referral to ICA by CCTA and diminishing ICAs indicated by an ischemia test.